When colleague got recognized: Third-party’s reaction to witnessing employee recognition - Yang, Tianfei; Jiang, Xia (Frontiers in Psychology, 2023)
Employee recognition, an incentive method widely used in management practice, plays an important role in the organization. Although extant studies have confirmed its effectiveness, little attention has been paid to its spillover effect. Based on the Social Cognitive Theory and Affective Events Theory, this study argues that employee recognition encounter can trigger cognitive and behavioral reactions. Through perceived organizational justice and workplace wellbeing, a chain-mediating effect connects witnessing employee recognition to work engagement. This research adopts the empirical research method by asking the participants to do the weekly survey (four times in 1 month), and 258 samples are collected. Using SPSS20.0 and its PROCESS macro module, hypotheses are tested. The results indicate (1) employees who witness leaders’ recognition of colleagues will (a) perceive higher organizational justice and (b) be more engaged in work. (2) Perceived organizational justice will mediate the positive relationship between employee recognition encounters with (a) workplace wellbeing and (b) work engagement. (3) Perceived organizational justice and workplace wellbeing will have a chain-mediating effect in the path of employee recognition encounter and work engagement. The results provide both practical and theoretical contribution to employee recognition.